Evaluation of fully automated a priori MCO treatment planning in VMAT for head-and-neck cancer. (July 2021) - Biston, Marie-Claude; Costea, Madalina; Gassa, Frédéric; Serre, Anne-Agathe; Voet, Peter; Larson, Randy; Grégoire, Vincent
Highlights: First evaluation of fully automated a priori- MCO treatment planning for HN cancer. A priori- MCO treatment planning provides a single Pareto-optimal plan per patient. Pareto- optimal plans are generated using a single wish-list per clinical protocol. A priori- MCO treatment planning was overall superior compared to manual plans. A priori- MCO treatment planning required no post-optimization manual intervention. Abstract: Purpose: Automated planning techniques aim to reduce manual planning time and inter-operator variability without compromising the plan quality which is particularly challenging for head-and-neck (HN) cancer radiotherapy. The objective of this study was to evaluate the performance of an a priori-multicriteria plan optimization algorithm on a cohort of HN patients. Methods: A total of 14 nasopharyngeal carcinoma (upper-HN) and 14 "middle-lower indications" (lower-HN) previously treated in our institution were enrolled in this study. Automatically generated plans (autoVMAT) were compared to manual VMAT or Helical Tomotherapy planning (manVMAT-HT) by assessing differences in dose delivered to targets and organs at risk (OARs), calculating plan quality indexes (PQIs) and performing blinded comparisons by clinicians. Quality control of the plans and measurements of the delivery times were also performed. Results: For the 14 lower-HN patients, with equivalent planning target volume (PTV) dosimetric criteria and dose homogeneity, significant decrease in the mean doses to the oral cavity, esophagus, trachea and larynx were observed for autoVMAT compared to manVMAT-HT. Regarding the 14 upper-HN cases, the PTV coverage was generally significantly superior for autoVMAT which was also confirmed with higher calculated PQIs on PTVs for 13 out of 14 patients, whereas PQIs calculated on OARs were generally equivalent. Number of MUs and total delivery time were significantly higher for autoVMAT compared to manVMAT. All plans were considered clinically acceptable by clinicians. Conclusions: Overall superiority of autoVMAT compared to manVMAT-HT plans was demonstrated for HN cancer. The obtained plans were operator-independent and required no post-optimization or manual intervention.